Enhanced Beam‐Steering‐Based Diagonal Beamforming Algorithm for Binaural Hearing Support Devices. Issue 7 (23rd December 2013) - Lee, Jun Chang; Nam, Kyoung Won; Cho, Kyeongwon; Lee, Sangmin; Kim, Dongwook; Hong, Sung Hwa; Jang, Dong Pyo; Kim, In Young
Abstract In order to improve speech intelligibility for hearing‐impaired people in various listening situations, it is necessary to diversify the possible focusing directions of a beamformer. In a previous report, the concept of binaural beam‐steering that can focus a beamformer in diagonal directions was applied to a binaural hearing aid; however, in the previously proposed protocol, the effective frequency range for consistent diagonal beam‐steering was limited to the 200–750 Hz range, which is far narrower than that of normal speech signals (200–4000 Hz). In this study, we proposed a modified binaural diagonal beam‐steering technique that can reduce the focusing‐direction deviations at high input frequencies up to 4000 Hz by introducing a new correction factor to the original protocol that can reduce the differences in gradient between the signal and the noise components at frequencies up to 4000 Hz. In simulation tests, the focusing effect of the proposed algorithm was more consistent than conventional algorithms. The deviations between the target and the focusing directions were reduced 27% in the left device and 6% in the right device with 45° steering at a 4000 Hz input signal, and were reduced 3% in the left device and 25% in the right device with 135° steering. On the basis of the experimental results, we believe that the proposed algorithm has the potential to help hearing‐impaired people in various listening situations.